VARIASI PENGGUNAAN VOLUME TABUNG UDARA TERHADAP EFISIENSI POMPA HIDRAM DUA KATUB LIMBAH - Muhammad Rusdi; Benny Kurniawan (Jurnal Magrobis, 2021)
Water is the source of life for living beings. One of the efforts to fulfillment of water demand, particularly in areas where the elevation is higher than the water source, using a hydram pump. At this time, the pump ttype was used is a pump with using an electric motor or diesel power, which is required a fuel oil so that require additional costs in the operation. To resolve this problem, the thought of appear to create an appropriate technology devices that is a hydram pump which does not use an electric motor power. Research aimed to determine the water debit and level of water flow out which is producet by air-tube variation volume, determine the efficiency of hydram by using variations volume of air tube. Research was conducted on August 2016 at Laboratory of Energy and Farm Machinery, Agricultural Engineering Studies Program, Sekolah Tinggi Pertanian (STIPER) Kutai Timur and tool testing on the area of East Kutai Agriculture College. Research method were used is analysis method and linear regression. The data was obtained through the testing will be analyzed by using empirical formulas that support calculation of data processing. Research results showed that the average efficiency of hydram pump according to D’Aubuission, on the volume of air-tube 1 amounted to 1,845%, volume of air-tube 2 amounted to 1,557&, volume of air-tube 3 amounted to 1,225%, and volume of air-tube 4 amounted to 0,923%.